Application of the Spectral-Shift Effect in the Small Lead-Based Reactor SLBR-50 - Zhao, Chen; Lou, Lei; Peng, Xingjie; Zhang, Bin; Wang, Lianjie (Frontiers in Energy Research, 2021)
In the design of a nuclear reactor, improving fuel utilization and extending burnup are two of the most important goals. A concept design of spectral-shift control rods is presented to extend cycle length and fuel utilization. First, a small lead-based reactor, SLBR-50, is preliminarily designed, and the design rationality is proved. Next, the concept design of spectral-shift control rods is presented and analyzed. Finally, numerical results of the small reactor design show that the burnup depth is extended by 73.3% and the fuel utilization rate for 235U and 238U is improved by 66.6 and 68.4%. All results are calculated using a Monte-Carlo code RMC. These results show advantages of the concept design for the spectral-shift control rod.